Beetle-like droplet-jumping superamphiphobic coatings for enhancing fog collection of sheet arrays. Issue 1 (2nd January 2020) - Wang, Xikui; Zeng, Jia; Yu, Xinquan; Liang, Caihua; Zhang, Youfa
Abstract : Fog collection from atmosphere is an effective way to solve the water resource crisis in arid or semi-arid areas. Abstract : Fog collection from atmosphere is an effective way to solve the water resource crisis in arid or semi-arid areas. Inspired by the bumpy surface of the desert beetle, this work provides a beetle-like superamphiphobic coating by adding silicon carbide particles to nano-SiO2 superamphiphobic coating in proportion, which shows excellent superamphiphobic performance, high nucleation rate, efficient drop removal efficiency and recommendable fog collection effect. In this work, drop removal is facilitated by the collisions of water droplets between the array sheets, and when the as-prepared samples are placed parallel to each other and with a space of ∼2 mm, the jumping drop collisions between two sample surfaces could promote the departure of droplets, and the water collection rate of the collision surface increased by ∼217% compared to that of the non-collision surface, which provides a new idea to promote water droplet removal. This work findings are instrumental in water collection and have wide application prospects in desalination, heat transfer, anti-fogging and other fields.